Protein-DNA interactions at the major and minor promoters of the divergently transcribed dhfr and rep3 genes during the Chinese hamster ovary cell cycle. - Wells, J (1996)
In mammals, two TATA-less bidirectional promoters regulate expression of the divergently transcribed dihydrofolate reductase (dhfr) and rep3 genes. In CHOC 400 cells, dhfr mRNA levels increase about fourfold during the G1-to-S phase transition of the cell cycle, whereas the levels of rep3 transcripts vary less than twofold during this time. To assess the role of DNA-binding proteins in transcriptional regulation of the dhfr and rep3 genes, the major and minor dhfr-rep3 promoter regions were analyzed by high-resolution genomic footprinting during the cell cycle. At the major dhfr promoter, prominent DNase I footprints over four upstream Sp1 binding sites did not vary throughout G1 and entry into the S phase. Genomic footprinting revealed that a protein is constitutively bound to the overlapping E2F sites throughout the G1-to-S phase transition, an interaction that is most evident on the transcribed template strand. On the nontranscribed strand, multiple changes in the DNase I cleavage pattern are observed during transit through G1 and entry into the S phase. By using gel mobility shift assays and a series of sequence-specific probes, two different species of E2F were shown to interact with the dhfr promoter during the cell cycle. The DNA binding activity of one E2F species, which preferentially recognizes the sequence TTTGGCGC, did not vary significantly during the cell cycle. The DNA binding activity of the second E2F species, which preferentially recognizes the sequence TTTCGCGC, increased during the G1-to-S phase transition. Together, these results indicate that Sp1 and the species of E2F that binds TTTGGCGC participate in the formation of a basal transcription complex, while the species of E2F that binds TTTCGCGC regulates dhfr gene expression during the G1-to-S phase transition. At the minor promoter, DNase I footprints at a consensus c-Myc binding site and three Sp1 binding sites showed little variation during the G1-to-S phase transition. In addition to protein binding at sequences known to be involved in the regulation of transcription, genomic footprinting of the entire promoter region also showed that a protein factor is constitutively bound to the first intron of the rep3 gene.